2009
DOI: 10.1103/physrevlett.102.057205
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity Approach to the Disordered QuantumXYModel

Abstract: We study the random XY spin chain in a transverse field by analyzing the susceptibility of the ground state fidelity, numerically evaluated through a standard mapping of the model onto quasifree fermions. It is found that the fidelity susceptibility and its scaling properties provide useful information about the phase diagram. In particular it is possible to determine the Ising critical line and the Griffiths phase regions, in agreement with previous analytical and numerical results.Introduction.-In the last f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 20 publications
3
68
0
Order By: Relevance
“…͑7͔͒, and especially the associated fidelity metric ͓Eq. ͑10͔͒, have been shown to be sensitive indicators of continuous transitions, [26][27][28][29][30][31][32][33] and we will see below that these also track level crossings quite well, as in general g exhibits a jump in those cases.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…͑7͔͒, and especially the associated fidelity metric ͓Eq. ͑10͔͒, have been shown to be sensitive indicators of continuous transitions, [26][27][28][29][30][31][32][33] and we will see below that these also track level crossings quite well, as in general g exhibits a jump in those cases.…”
Section: Introductionmentioning
confidence: 96%
“…The ground-state fidelity, originally studied in the context of quantum information theory, has been shown to be a sensitive indicator of changes in the ground state of manybody systems, as they occur in quantum phase transitions. [26][27][28][29][30][31][32][33][34] The other two observables of interest we will study are the d-wave and extended-s-wave superconductivity condensate occupations. They will be defined carefully in the next section.…”
Section: Introductionmentioning
confidence: 99%
“…Reversing the randomness behavior of the coupling constant and the field with respect to the spin glass Hamiltonian leads to the quantum XY model with a random transverse field (see [27,52] and references therein), with the Hamiltonian Finally, we consider the case of the one-dimensional quantum XY spin glass with random transverse magnetic fields h i applied in the z-direction (see [27,29,[53][54][55][56] and references therein). The Hamiltonian for this model is given by…”
Section: Quantum Xy Model With Random Transverse Magnetic Fieldmentioning
confidence: 99%
“…In ref. 26 the authors applied the fidelity approach to estimate random transitions of a disordered quantum model. They showed that the fidelity susceptibility and its scaling properties provide useful information about the phase diagram.…”
Section: Introductionmentioning
confidence: 99%